Formalisasi Mutu Berbasis Legitimasi Ideologis dalam Manajemen Pendidikan Islam di Madrasah Ibtidaiyah - Andika Febriyanto Kahfi; Sabarudin; Dinda Agustiana; Awla Putri Adibah (Advances In Education Journal, 2026)
This study aims to analyze the relationship between Islamic educational ideology, power relations, and the quality of Islamic educational management in the administration of Madrasah Ibtidaiyah. The study is motivated by the tendency of educational management practices to prioritize administrative aspects over the internalization of Islamic ideological values in decision-making processes and institutional governance. This research employed a qualitative approach using a case study design. The research subjects consisted of the principal, teachers, and administrative staff selected purposively based on their involvement in institutional managerial processes. Data were collected through in-depth interviews, observations, and documentation, and were analyzed using thematic analysis through the stages of open coding, axial coding, and selective coding. The findings reveal that Islamic educational ideology functions as a normative foundation in madrasah management practices through the values of tawhid, trustworthiness, justice, deliberation, and ihsan. However, the implementation of these values is influenced by the power relations within the institution. Participatory power structures tend to encourage transparent and collaborative managerial practices, whereas administrative and centralized domination of power potentially shifts the orientation of educational quality toward formalistic practices. This study also proposes an integrative model illustrating the interconnection between ideology, power relations, managerial practices, and the quality of Islamic educational management in a holistic manner. Therefore, strengthening the quality of Islamic education requires the integration of ideological values into every managerial practice in order to establish substantive and sustainable educational governance.